Neuropsychological Effects of Anticonvulsants - Lindsey Morgan; Alexandra Shaw (Pediatric Neurology Briefs Publishers, 2015)
Investigators from 7 centers in Korea conducted a prospective, multicenter study with patients randomized into two open-label, parallel groups and treated with either levetiracetam (LVT) or carbamazepine (CBZ) monotherapy for newly diagnosed focal epilepsy.